2018
DOI: 10.3847/1538-4357/aaedbd
|View full text |Cite
|
Sign up to set email alerts
|

MAGiiCAT VI. The Mg ii Intragroup Medium Is Kinematically Complex

Abstract: By comparing Mg II absorption in the circumgalactic medium (CGM) of group environments to isolated galaxies, we investigated the impact of environment on the CGM. A Mg II absorber is associated with a group if there are two or more galaxies at the absorption redshift within a projected distance of D = 200 kpc from a background quasar and a line-of-sight velocity separation of 500 km s −1 . We compiled a sample of 29 group environments consisting of 74 galaxies (2 − 5 galaxies per group) at 0.113 < z gal < 0.88… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
78
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 87 publications
(150 reference statements)
14
78
3
Order By: Relevance
“…Bordoloi et al (2011) found marginally more extended Mg ii absorption profiles compared to a sample of more isolated galaxies, concluding that the absorbing gas is more likely to be associated to the individual galaxies rather than the intragroup medium. Nielsen et al (2018) similarly found an enhanced equivalent width of Mg ii absorbers in a sample of 29 galaxy groups with respect to an isolated galaxy sample. These authors have complemented these results with a kinematical analysis of the absorption profiles and concluded that the absorbers originate from an intragroup medium rather than from individual galaxies.…”
Section: A High Fraction Of Strong Mg II Absorbers In Galaxy Groupsmentioning
confidence: 70%
See 1 more Smart Citation
“…Bordoloi et al (2011) found marginally more extended Mg ii absorption profiles compared to a sample of more isolated galaxies, concluding that the absorbing gas is more likely to be associated to the individual galaxies rather than the intragroup medium. Nielsen et al (2018) similarly found an enhanced equivalent width of Mg ii absorbers in a sample of 29 galaxy groups with respect to an isolated galaxy sample. These authors have complemented these results with a kinematical analysis of the absorption profiles and concluded that the absorbers originate from an intragroup medium rather than from individual galaxies.…”
Section: A High Fraction Of Strong Mg II Absorbers In Galaxy Groupsmentioning
confidence: 70%
“…Several studies have used the Mg ii doublet to trace gas with similar column densities to that detected through 21-cm atomic hydrogen observations (e.g. Bergeron 1986;Kacprzak et al 2008;Steidel et al 1994;Chen & Tinker 2008;Chen et al 2010;Gauthier 2013;Bordoloi et al 2014a;Nielsen et al 2015;Schroetter et al 2016;Nielsen et al 2018;Rubin et al 2018a,b). These studies have found that Mg ii absorbers trace the CGM of galaxies and possibly outflowing gas up to a distance of ∼ 100 kpc (Kacprzak et al 2008;Chen et al 2010).…”
mentioning
confidence: 99%
“…Lanzetta & Bowen 1990;Bergeron & Boissé 1991;Bouché et al 2006;Chen et al 2010). We compared our groups to several other MUSE studies from the literature and the Mg ii absorbers compilation MAG iiCAT (Nielsen et al 2013) of isolated galaxies as well as galaxy groups (Nielsen et al 2018). Fig.9 shows that MUSE-ALMA Halos systems are in agreement with this relation, especially with other absorption-related groups.…”
Section: Absorbers Are Associated With Multiple Galaxiesmentioning
confidence: 99%
“…Combined with highresolution UV spectroscopy of quasars, these studies have revealed relevant features interpreted as galactic outflows (Schroetter et al 2016;Rahmani et al 2018b;Schroetter et al 2019), warped accretion discs (Rahmani et al 2018a) and galactic fountains (Bouché et al 2016). Alongside the detection of kinematic traces of gas inflows and outflows, new studies detected multiple galaxies associated with one absorber (Bielby et al 2017;Péroux et al 2017;Klitsch et al 2018;Nielsen et al 2018;Péroux et al 2019;Muzahid et al 2019). These findings point towards a more complex view of the gaseous halos of galaxies: from the halo gas of single systems, through tidal streams and halo substructures (Whiting et al 2006; Kacprzak et al 2010) to intra-group gas (Bielby et al 2017;Fossati et al 2019).…”
mentioning
confidence: 99%
“…RomulusC is among the highest resolution hydrodynamic cosmological simulations of a galaxy cluster run to date, with a Plummer equivalent gravitational force resolution of 250 pc (a 350 pc spline kernel is used), a maximum SPH resolution of 70 pc, and gas and dark matter mass resolutions of 2.12 × 10 5 and 3.39 × 10 5 M respectively. At this resolution, RomulusC is one of only two cluster cosmological simulations currently in production that is capable of resolving the multiphase structure of gas in the ICM (see also Nelson et al (2019)). Lower mass halos and galaxies, including their interaction with the ICM, are also followed The color scaling of the images in the bottom row is roughly consistent with the sensitivity of existing instruments.…”
Section: The Romulusc Simulationmentioning
confidence: 99%